Strengthening the Character of Nationalism through School Culture at SMP Negeri 1 Serasan Timur - Ariya Winandar; Amrazi Zakso; Thomy Sastra Atmaja; Sulistyarini, Sulistyarini; Tri Utami (STKIP Taman Siswa Bima, 2025)
This study aims to examine how the reinforcement of nationalism character is cultivated through school culture at SMP Negeri 1 Serasan Timur. The research employed a qualitative method with a descriptive approach. The subjects of this study were the principal, the vice principal for student affairs, the Civics Education teacher, and students. Data were collected through interviews, observations, and documentation, and analyzed using Miles and Huberman’s model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the reinforcement of nationalism character is implemented through various routine activities, such as weekly flag ceremonies on Mondays, singing the national anthem before lessons, playing national songs during school hours, scout extracurricular activities, and commemorating Independence Day through carnivals and competitions. Spontaneous activities are reflected in teachers’ actions to resolve student conflicts, giving sanctions to students who engage in discriminatory behavior related to ethnicity, religion, or race, as well as acts of bullying, and in the solidarity of the school community when providing assistance to those affected by misfortune or visiting sick teachers and students. Role modeling is demonstrated by teachers through attitudes that do not discriminate based on ethnicity, religion, race, culture, or social status, as well as by promoting the use of local products and consistently using the Indonesian language within the school environment. Conditioning is also evident in the display of the President, Vice President, and National Emblem photographs, along with the implementation of wearing batik and traditional Malay attire at school.